The formation of hybrid identity of the Kurds and Turks through interethnic marriages in Turkey - Altaş, Tuğba (My University, 2018)
Identities are not "fixed and innate" but "fluid and multiple", formed out of the interactions with others; so each encounter adds new meanings to the identities. Based on different theories of the identity, the study aims to show the changing nature of the identity shaped by the processes of migration, globalization and interethnic marriages. The objective of this research is to shed light on the terms, in particular ―hybridity, in-betweenness and ambivalence‖ and to connect them to the Kurds and the Turks who have become ethnically hybrids due to marriages between the Kurds and the Turks. Hybridity, developed from botanical and biological origins has started to be used as mixing of cultures of the colonized and the colonizer groups, in particular during post-colonialism. Hence, the study pursues to indicate hybridization of the identities and explores the processes of hybridization of the Kurds and the Turks through interethnic marriages in Turkey. The main question of the thesis is whether the hybrid Kurds and Turks consider themselves biethnic/bicultural or not. If so, it is assumed these hybrids will approach Kurdish and Turkish nationalism differently. In other words, rather than focusing on differences, they will concentrate on similarities and sharings, and they will be more willing to live together. Hence, in the research paper firstly, it is important to give information about what identity, hybridity and globalization are, and whether there are any marriages between the Turks and the Kurds or not. Soon, what hybridity was in the 19th century and is now will be clarified. Finally; with interviews, the thoughts of hybrids about their identity will be given. Data consist of 15 qualitative interviews conducted with the individuals at different ages and different jobs in Erzurum, Bursa and Istanbul. The main purposes of the study are to find how these people define themselves: whether as Kurds, Turks, in-between, or both, and to examine whether they have any differences from non-hybrid Turks and Kurds, and to see their approach to the Kurdish and Turkish nationalism.

Başkalarıyla etkileşim sonucu oluşan kimlikler "sabit ve doğuştan" değil "akışkan ve çoklu" durlar; bu yüzden her bir karşılaşma kimliklere yeni anlamlar katar. Farklı kimlik teorilerine dayanan bu çalışma; göç, küreselleşme ve etnik kimlikler arası evlilik süreçleriyle şekillenen kimliğin değişken doğasını göstermeyi hedeflemektedir. Araştırmanın amacı, özellikle "melezlik, aradakalmışlık ve duygu karmaşası" terimlerini aydınlatmak ve bunları Kürtler ve Türkler arasındaki evliliklerden dolayı etnik olarak melezleşmiş Kürtlere ve Türklere bağlamaktır. Botanik ve biyolojik kökenden gelişen melezlik, özellikle postkolonyal dönemde sömüren ve sömürülen grupların kültürlerinin karışması olarak kullanılmaya başlanmıştır. Bu yüzden, bu çalışma kimliklerin melezleşmesini göstermeyi ve Türkiye‘de etnik kimlikler arası evlilikle Kürtlerin ve Türklerin melezleşme süreçlerini keşfetmeyi hedeflemektedir. Tezin ana sorusu melez Kürt ve Türklerin kendilerini iki etnikli/ iki kültürlü sayıp saymadıklarıdır. Şayet böyleyse, bu melezlerin Kürt ve Türk milliyetçiliğine farklı yaklaşacakları varsayılmaktadır. Diğer bir deyişle, farklılıklara odaklanmaktansa, benzerlikler ve paylaşımlar üzerine odaklanacak ve birlikte yaşamaya daha çok istekli olacaklardır. Dolayısıyla, araştırma metninde ilk önce kimlik, melezlik ve küreselleşmenin ne olduğu ve Türkler ve Kürtler arasında evliliklerin olup olmadığı hakkında bilgi vermek önemlidir. Daha sonra, melezliğin 19. yüzyılda ve şuanda ne olduğu açıklanacaktır. Son olarak, mülakatlarla bireylerin kimlikleri hakkındaki düşünceleri verilecektir. Veriler, Erzurum, Bursa ve İstanbul'daki farklı yaşlarda ve mesleklerde bulunan kişilerle yapılmış 15 nitel mülakattan oluşmaktadır. Tezin asıl amaçları; bu insanların kendilerini nasıl tanımladıklarını - Kürt, Türk, aradakalmış veya ikisi birden olarak mı- bulmak ve melez olmayan Kürt ve Türklerden farklılıklarının olup olmadığını incelemek ve Kürt ve Türk milliyetçiliğine karşı tutumlarını görmektir.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2018
Keywords: Hybridity; In-betweenness; Ambivalence; Identity; Nationalism